Role of Sequence Variations in AhR Gene Towards Modulating Smoking Induced Lung Cancer Susceptibility in North Indian Population: A Multiple Interaction Analysis - Budhwar, Sneha; Bahl, Charu; Sharma, Siddharth; Singh, Navneet; Behera, Digambar (Current Genomics, 2018)
Background: AhR, a ubiquitously expressed ligand-activated transcription factor, upon its encounter with the foreign ligands activates the transcriptional machinery of genes encoding for biotransformation enzymes like CYP1A1 hence, mediating the metabolism of Poly aromatic hydrocarbons and nitrosamines which account for the maximally found carcinogen in cigarette smoke. Polymorphic variants of AhR play a significant role and are held responsible for disposing the individuals with greater chances of acquiring lung cancer. Objective: To study the role of AhR variants (rs2282885, rs10250822, rs7811989, rs2066853) in affecting lung cancer susceptibility. Methods: 297 cases and 320 controls have been genotyped using PCR-RFLP technique. In order to find out the association, unconditional logistic regression approach was used. To analyze high order interactions Multifactor Dimensionality Reduction and Classification and regression tree was used. Results: Subjects carrying the variant genotype for AhR rs7811989 showed a two-fold risk (p=0.007) and a marginal risk was also seen in case of individuals carrying either single or double copy of susceptible allele for rs102550822 (p=0.02). Whereas the variant allele for rs2066853 showcased a strong protective effect (p=0.003). SQCC individuals with mutant genotype of rs2066853 also exhibited a protective effect towards lung cancer (OR=0.30, p=0.0013). The association of rs7811989 mutant genotype and rs10250822 mutant genotype was evident especially in smokers as compared to nonsmokers. AhR rs2066853 showed a decreased risk in smokers with mutant genotype (p=0.002). MDR approach gave the best interaction model of AhR rs2066853 and smoking (CVC=10/10, prediction error= 0.42). Conclusion: AhR polymorphic variations can significantly contribute towards lung cancer predisposition.
Keywords: Lung cancer